Uncommon causes of ischaemic stroke: how to approach the diagnosis. Issue 1 (21st July 2022) - Hurford, Robert; Siripurapu, Rekha; Emsley, Hedley C A; Lovett, Joanna; Werring, David; Punter, Martin Nicholas Michael
Abstract : Stroke is a common neurological emergency and although most cases are associated with traditional vascular risk factors leading to cerebral ischaemia by well-recognised pathophysiological mechanisms, around 4% of ischaemic strokes are due to rare conditions. These are important to recognise due to their different management, which is often specific and effective, and due to their different prognosis from otherwise cryptogenic ischaemic strokes. We outline a practical approach to identifying uncommon causes of ischaemic stroke by highlighting diagnostic 'red flags' and propose a structured approach to investigating them.